Three new species of Pseudoceraphron from Japan and New Zealand (Hymenoptera: Chalcidoidea: Pteromalidae) - Jałoszyński, Paweł (Zootaxa, 2020)
The leaf-litter-inhabiting diparine genus Pseudoceraphron Dodd (Hymenoptera: Pteromalidae) is for the first time recorded to occur in the Northern Hemisphere (Japan) and is confirmed from New Zealand. Pseudoceraphron belissimus sp. n. (Japan: Ishigaki-jima), P. zealandicus sp. n., and P. kepanus sp. n. (both New Zealand: Northern Island) are described.